Self-detection system based on gene amplification and method - ZHAO ZIRU; CHU HAITAO (2018)
The invention provides a self-detection system based on gene amplification. The system comprises a self-sampling device, a gene detection reagent component, a gene amplifier and a mobile client, wherein the self-sampling device is used for enabling a subject to extract a gene detection sample by self; the gene detection reagent component is used as a container component for sample treatment, sample transfer and gene amplification reaction of the gene detection sample; the gene amplifier is used for providing reaction conditions of sample treatment and gene amplification reactions and used foroutputting recognizable reaction result information; the mobile client is used for storing an operation instruction program, used for transmitting recognizable reaction result information to a serverand used for receiving a judgment result of the recognizable reaction result information, wherein the judgment result is fed back by the server. The system is a set of gene self-detection system whichdoes not depend on profess